CONTENT OF MMP-9 IN SERUM, SALIVA, TISSUES IN PATIENTS WITH CYST OF THE MAXILLARY SINUS - Naumenko, O.; Deeva, J.; Rezmac, M. (The Ukrainian Scientific Medical Youth Journal, 2018)
Department of Otorhinolaryngology Bogomolets National Medical University 125 patients with a cyst of the maxillary sinus were observed. The aim of the study was to determine the content of MMP-9 in the preoperative period in saliva, serum, in the shell of a cyst, which was removed from the maxillary sinus. The data obtained in our study indicate the relationship between such pathology as a cyst of the maxillary sinus and an increasing the level of MMP-9 in the saliva of the examined patients. Most patients who showed an increase of the content of MMP-9 in saliva also showed an increase of the level of MMP-9 in the cyst envelope. It can be assumed that the increase of MMP-9 in saliva is due precisely to the course of latent, asymptomatic periodontitis.